P117 Rituximab therapy for primary Sjögren's syndrome – a retrospective single-centre study. (23rd March 2020) - Figueiras, Mariana; Sousa, Filipa; Brandão, Mariana; Oliveira, Daniel; Faria, Raquel; Campar, Ana; Almeida, Isabel; Marinho, António; Farinha, Fátima; Vasconcelos, Carlos
Abstract : Background: The rationale for B cell depletion therapy with rituximab (RTX) in primary Sjögren's syndrome (pSS) relies upon the well-established role of B cell hyperactivity in immunopathogenesis. We reviewed our centre's experience in efficacy, tolerability and safety of RTX in pSS patients. Methods: Retrospective single-centre (35 years long, 115 pSS patients cohort) observational study of RTX use in pSS adults from 2006 until September 2019, based on medical records, with data concerning indication and duration of treatment. Outcomes were assessed by subjective physician's perspective, ESSDAI variation, drug reactions, infections, neutrophil count, immunoglobulin and B-cell count. ESSDAI scores were calculated for pre and post whenever possible. Results: Ten female pSS patients were treated with RTX, with an average diagnosis age of 50, 7 years and an average follow-up time of 5, 6 years. Indications for RTX were: 3 peripheral nervous system (NS) manifestations, 3 central NS manifestations, 1 vasculitis, 1 vasculitis, central NS and macrophagic activation syndrome, 1 disabling musculoskeletal manifestations and 1 interstitial lung disease. Six patients became asymptomatic (4 of them with CD19 depletion), 2 did not experienced any benefit (1 with CD19 depletion) and 2 had symptomatic improvement (1 with CD19 depletion). Two patients had severe adverse reactions to rituximab (anaphylactic reaction and sweet syndrome). Although they needed hospital admission, they were able to recover completely. Three patients developed serum sickness. There were no cases of hypogammaglobulinemia or neutropenia after the treatment. Conclusions: Despite of the scarcity of studies validating its use, RTX can be considered for severe or refractory pSS involvement, with a reasonable safety profile.